Dynamics of Selected Haematological and Biochemical Parameters in Blood of Calves in Relation to Environmental Conditions - Miloslav Šoch; Luboš Zábranský; Bohuslav Čermák; Pavel Novák; Jan Brouček; Karel Suchý; Anna Šimková; Kateřina Švejdová; Anna Švarcová; Tomáš Freilach; Michal Benda (Scientific Papers Animal Science and Biotechnologies, 2023)
The health status of calves is very important for the future production of meat and dairy cattle. The aim of this thesis is to evaluate the dynamics of selected hematologic and biochemical parameters in blood plasma of calves reared in different environmental conditions. Totally 120 blood samples of calves in age of 1 to 124 days were collected. The animals came from three different breeds with different ways of rearing. The total blood parameters tested in all observed groups were in the normal range. Dynamics of selected hematologic and biochemical parameters in blood plasma of calves in all groups were relatively similar. It is evident that the calves, while preserving the basic animal hygiene conditions of livestock, can cope with the effects of different technologies of rearing and environmental conditions.